2019
DOI: 10.1093/jme/tjz031
|View full text |Cite
|
Sign up to set email alerts
|

Development and Field Evaluation of a System to Collect Mosquito Excreta for the Detection of Arboviruses

Abstract: Mosquito-borne diseases are a major public health concern globally and early detection of pathogens is critical to implement vector management and control strategies. Existing methods for pathogen detection include screening sentinel animals for antibodies and analyzing mosquitoes for pathogen presence. While these methods are effective, they are also expensive, labor-intense, and logistically challenging. To address these limitations, a new method was developed whereby mosquito saliva is collected on honey-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…However, since this study was conducted, Ramirez et al () have found that detection of arboviruses in excreta under laboratory conditions was more sensitive compared to detection in saliva, and that excreta samples tested positive to arbovirus RNA within a much shorter time period following the ingestion of an infectious blood meal compared to mosquito saliva samples, where the intrinsic virus incubation period delayed rapid virus RNA detection. Using mosquito excreta for arbovirus detection has since been successfully tested in the field by Meyer et al (), with this method another potential alternative for rapid arbovirus detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, since this study was conducted, Ramirez et al () have found that detection of arboviruses in excreta under laboratory conditions was more sensitive compared to detection in saliva, and that excreta samples tested positive to arbovirus RNA within a much shorter time period following the ingestion of an infectious blood meal compared to mosquito saliva samples, where the intrinsic virus incubation period delayed rapid virus RNA detection. Using mosquito excreta for arbovirus detection has since been successfully tested in the field by Meyer et al (), with this method another potential alternative for rapid arbovirus detection.…”
Section: Discussionmentioning
confidence: 99%
“…To determine if viral genomes could be sequenced from excreta sampled from mosquitoes collected using the methods of Meyer et al ( 16 ), studies were conducted in Far North Queensland (FNQ) and South East Queensland (SEQ) in March and April 2018 ( Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, based on results obtained from sequencing mosquito excreta, virus detection and subsequent isolation could be attempted from the mosquito homogenates for viruses that can be grown in vitro . Use of traps that are highly selective for mosquitoes, such as CO 2 -baited passive box traps that do not deploy lights that attract other insects, is recommended ( 16 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations